2020
DOI: 10.1177/2332858420922841
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability and Maturation of School Turnaround: A Multiyear Evaluation of Tennessee’s Achievement School District and Local Innovation Zones

Abstract: Recent evaluations of reforms to improve low-performing schools have almost exclusively focused on shorter term effects. In this study, we extend the literature by examining the sustainability and maturation of two turnaround models in Tennessee: the state-led Achievement School District (ASD) and district-led local Innovation Zones (iZones). Using difference-in-differences models, we find overall positive effects on student achievement in iZone schools and null effects in ASD schools. Additional findings sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…The Turning Around Lowest-Achieving Schools (TALAS) program, funded through Race to the Top in NC, was found to have modest positive effects in some grades (Henry & Guthrie, 2019) but mostly null or negative effects (Heissel & Ladd, 2018). Pham and his colleagues (2019) found positive effects in Tennessee among Innovation Zone schools that were governed and managed separately by intradistrict networks. Two companion studies in Louisiana and Kentucky produced divergent findings of statewide turnaround efforts under NCLB waivers: The Louisiana analysis showed that, over each of 3 years, focus school reforms had no measurable impact on school performance (Dee & Dizon-Ross, 2019), whereas the Kentucky study found that focus school reforms led to substantial improvements in math and reading achievement (Bonilla & Dee, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…The Turning Around Lowest-Achieving Schools (TALAS) program, funded through Race to the Top in NC, was found to have modest positive effects in some grades (Henry & Guthrie, 2019) but mostly null or negative effects (Heissel & Ladd, 2018). Pham and his colleagues (2019) found positive effects in Tennessee among Innovation Zone schools that were governed and managed separately by intradistrict networks. Two companion studies in Louisiana and Kentucky produced divergent findings of statewide turnaround efforts under NCLB waivers: The Louisiana analysis showed that, over each of 3 years, focus school reforms had no measurable impact on school performance (Dee & Dizon-Ross, 2019), whereas the Kentucky study found that focus school reforms led to substantial improvements in math and reading achievement (Bonilla & Dee, 2017).…”
Section: Literature Reviewmentioning
confidence: 98%
“…While SIG reforms involved substantial investments, research findings on their near-term effects have been mixed (Dee, 2012; Dragoset et al, 2017; Sun et al, 2017). Although researchers in one study have started to compile 6-year postreform evidence for a similar turnaround initiative in Tennessee (Pham et al, 2019), no study that we know of has examined SIGs’ longitudinal effects beyond the three intervention years and across multiple locations. In this article, we examine the grants’ effects over 6 or 7 years on the first two SIG cohorts of 99 schools from four locations: North Carolina (NC), Washington State (WA), San Francisco Unified School District (SFUSD), and Beachfront County Public Schools (BCPS, pseudonym).…”
mentioning
confidence: 99%
“…Furthermore, research finds that different approaches to school turnaround vary in their effectiveness (Redding & Nguyen, 2020; Schueler et al, 2020). For example, one set of studies found that a turnaround model maintaining local governance with increased autonomy outperformed a state takeover model in which school management was largely turned over to charter management organizations (CMOs) (Henry et al, 2020, Pham et al, 2020). Schueler and Bleiberg's (2021) recent analysis of national data found substantial heterogeneity in the effectiveness of state takeovers between 2011 and 2016, with no impact, on average, on student achievement.…”
Section: Introductionmentioning
confidence: 99%
“…Tennessee is one state that presents a unique opportunity to fill this gap. Since 2012, Tennessee has implemented two distinct long-running school turnaround models, each involving the restructuring of local school governance and staff changes in low-performing schools with majority-Black student enrollment (Center for Research on Education Outcomes, 2018; Pham et al, 2020; Zimmer et al, 2017). In 2010, Tennessee passed its First to the Top Act.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation